Path Analysis of The Effect of Social Interaction, Emotional Intelligence, and Learning Interest on Students' Mathematics Learning Achievement - Sanbein, Anita Fanu; Salsinha, Cecilia Novianti; Naimnule, Maria (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
Students' emotional intelligence and very low social interaction, as well as students' declining interest in learning in class X, are important problems found at SMA Negeri 2 Kefamenanu. For this reason, the researcher wanted to find out how much influence social interaction had on learning achievement with or without moderation variables, namely emotional intelligence and learning interest, as well as the influence of the selected moderation variables. This type of research is a quantitative research with a survey method. The results of the study were then analyzed with path analysis statistics. The subjects in this study are students in class X of SMA Negeri 2 Kefamenanu. The types of data used in this study are primary data and secondary data. The results showed that the biggest influence was the direct influence of emotional intelligence on learning achievement at 62.41%. In addition, there was a direct influence of social interaction on learning achievement by 43.56%. This research provides implications for educators to improve student learning achievement through social interaction and emotional intelligence. This also shows the novelty of the results of the analysis, that emotional intelligence turns out to be more influential on student achievement than learning interest.